Analysis Of The Effectiveness And Efficiency Of The Internal Control System For The Supply Of Medicines In Public Hospitals Sinar Husni - Cyntia Amelia Siregar; Yenni Samri Juliati Nasution; Nurwani Nurwani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The internal control system will help hospitals minimize risks arising from medicine supplies, such as damage, loss, theft and shortages of supplies which can disrupt hospital service activities in terms of medicine availability. The aim of this research is to analyze the internal control system for medicine supplies at the Sinar Husni General Hospital. This research approach is descriptive using qualitative data types. Data collection methods were carried out by interviews and literature studies. The research subjects were the pharmacist in charge and pharmacy warehouse assistant at Sinar Husni General Hospital. The results of the research show that the internal control system for medicine supplies at Sinar Husni General Hospital has not been implemented effectively and efficiently so it is not in accordance with the objectives of internal control. This is proven by the existence of control elements that have not been implemented optimally, namely the risk assessment element, control activities, and information and communication.